Coping with Aridity: Life History of Chacophrys pierottii, a Fossorial Anuran of Gran Chaco - Marangoni, Federico (2018)
We studied size, age and growth in Chacophrys pierottii, a fossorial amphibian inhabiting the arid region of Gran Chaco, in Northern Argentina. We provide the first detailed demographic data for this cryptic species using skeletochronology. We observed a female-biased sexual size dimorphism, but no differences in age parameters between the two sexes. C. pierottii has a short life span of up to five years, both males and females reaching sexual maturity after one year. Our results suggest that the rapid growth to maturity, followed by a relatively short reproductive lifespan, is a response to the constraints posed by arid environments. The life-history parameters in the studied population of C. pierottii are in line with the observed patterns of other anurans inhabiting xeric habitats. Our study provides conservation managers with the basic data required for the accurate assessment of the species status and the adoption of proper conservation strategies.